Bioenergy generation from agricultural wastes and enrichment of end products - Gupta G.K.; Mondal M.K. (My University, 2025)
At present, conventional fuels (coal, petroleum, and natural gas) are the prime energy sources, but their use at a frightening rate has created a fear of their depletion by the next 70 years. Thus there is a need to think for an alternative energy source, and among various sources, utilization of agricultural wastes (rice husk, wheat straw, corn cob, etc.) to useful products has gained much attention. Based on the biomass properties (fiber analysis, proximate and ultimate analysis, high heating value, etc.), different routes for biomass conversion can be decided. For biological conversion, a lesser amount of lignin is preferred so that it can be degraded easily at a lower temperature. The end products include biogas (CH4, CO2, H2S) and useful alcohols. For thermochemical conversion, woody biomass (not easily degradable) is preferred. Gasification produces H2, CO, CH4, and CO2 and traces of other gases. Pyrolysis leads yield of three useful products (biooil, biochar, and pyrolytic gas). Biogas can be enriched by using absorption technique where CO2 and H2S can be removed from the stream. For gasification, exit gas should be passed through a cyclone separator in connection with water scrubber, where NH3 and HCl are washed followed by ZnO guard for H2S and an active carbon filter for traces of NH3, HCl, etc. The enrichment of products from pyrolysis includes different processes, such as hydrocracking, hydrotreating, esterification, emulsification, and catalytic pyrolysis. The end products have utilities in different fields and can become a substitute for the available conventional energy resources. © 2020 Elsevier Inc. All rights reserved.